Silvicultura de Pinus elliottii Engelm no litoral sul do Rio Grande do Sul: efeitos no solo e no lençol freático - Zwetsch, Ana Paula Reis (2023)
The forestry of Pinus elliottii Engelm expanded in the state of Rio Grande do Sul (RS), based on tax incentives in the 70s, including in the coastal region of the Pampa. However, currently researchers and environmentalists are questioning the viability of this activity, since some studies have shown possible negative impacts on soil, water, fauna, flora and others. Therefore, this work aimed to study the effect of pine forestry on soil and groundwater. The work was developed in the experimental area of the project entitled Fazenda Modelo Flopal, in the municipality of Santa Vitória do Palmar-RS. In relation to the soil, the physical and chemical attributes were evaluated in a completely randomized, bifactorial design of 3 x 5, in the area of Pinus Mar, Native Vegetation and Pinus Lagoa , at depths 0-5 cm, 5-10 cm, 10-20 cm, 20-40 cm and 40-100 cm, for the variables density, total porosity, macro and microporosity, percentage of clay, pH/ H2O, phosphorus, potassium, percentage of organic matte, aluminum, calcium, magnesium, effective CTC with pH 7.0, hydrogen and aluminum , percentage of CTC saturation by bases and aluminum, sulfur, zinc, copper, boron, manganese. It was observed that there was a statistical difference in relation to macroporosity and microporosity regarding the location and depths, presenting better results for the silviculture of Pinus elliottii for soil physics and the other variables did not differ from each other. For soil chemistry there were several elements that varied in depth and location, except K. For the analysis of groundwater, 16 piezometers were drilled, which were monitored with a level meter (Jacirí) from Solinst ® periodically, and in 4 of these wells was instrumented with a levelogger sensor from Sigma Sensors®, with data collection every 15 min. From this, it was possible to calculate the distribution of the levels, preparation of the curves of total permanence and by summer period and also to evaluate the recharge by the WTF (Water Table Fluctuaction) method. From the information obtained it is possible to affirm that the silviculture of Pinus elliottii Engelm in the study area did not generate alteration in the dynamics of the groundwater in comparison with the native vegetation of the Coastal Plain.